Suture needles in Oral Surgery: Alterations depending on the type and number of sutures - Torres-Lagares, Daniel (Medicina Oral S.L., 2012)
This study examined whether the number and type of sutures used in oral surgery influence two ad hoc variables (incision plane and displaced area), which are two variables related to whether the suture needle is suitable for the task. Seventy-five TB-15 needles were studied, which were used to suture between zero and three mucosa and/subperiosteal sutures, producing 15 groups with 5 needles in each one. The incision plane and displaced area were measured for each group, which are two variables related to how the needle has worn and altered. Statistical treatment was conducted using the Kruskal-Wallis H test to compare multiple values and the Mann-Whitney U test to compare pairs. A multi-stage regression model was applied with the aim of predicting the changes in the dependent variables based on the number and type of sutures performed. The incision plane ranged from 126.67 to 346.24μm among the different groups. The displaced area was measured as being between 14 524.83μm² and 128 311.91μm². The best predictive model for the incision plane obtained a coefficient of determination (R2) of 0.149, while it reached 0.249 for the displaced area. Subperiosteal sutures held more weighting among the variables studied. Mucosal sutures did not seem to greatly affect needle wear. Observations reported in this paper indicate that the needle should be changed after having performed two subperiosteal sutures, given the wear and change to the incision plane that is produced, which causes the needle’s cutting ability to reduce. Key words: Needles, sutures, material testing, oral surgery, third molar, scanning electron microscope.